Indonesian Stock Market Reaction: Effects of Uncertainty Policy Shocks in the United States and China - Rilmia Oktavian; Alvin Sugeng Prasetyo (Department of Development Economics, Universitas Sriwijaya, 2023)
The purpose of this study is to examine and analyze the effect of economic policy uncertainty US and China on the Indonesian stock market. The data uses time series, from January 2000-July 2022. The methods used are the Structural Vector Error Correction Model (SVECM). The results show that the uncertainty of the US and China's economic policies has a negative and significant effect on the Indonesian stock market. The response of Indonesian stock market responded negatively to the economic policy uncertainties of the US and China. The results of the study show that the uncertainty of the US and China's economic policies has a negative and significant effect on the Indonesian stock market. The response of Indonesian stock market responded negatively to the economic policy uncertainties of the United States and China. The results of the study show that the uncertainty of the US and China's economic policies has a negative and significant effect on the Indonesian stock market. Indonesian stock market responded negatively to the economic policy uncertainties of the United States and China.